Find the First and Second Derivative of:

f(x)=(x+5)/(2x-4)

Rewrite and use the product rule:

f(x)=(x+5)(2x-4)^-1

f'(x)=(x+5)((2x-4)^-1)' + (x+5)'(2x-4)^-1

f'(x)=(-2)(2)(x+5)(2x-4)^-2+(1)(2x-4)^-1

<<<<<<<<< the factor (2) is wrong
After Simplifying:

f'(x)=-4x^2-12x+40/(2x-4)^2

At this point do I simplify further by making the denominator a polynomial or do I keep it within it's brackets?

f'(x)=-4x^2-12x+40/(2x-4)(2x-4)

f'(x)=-4x^2-12x+40/4x^2+16

Then do I divide the numerator and denominator?

f'(x)= x^2-12x+(5/2)

I have to find the second derivative, so I want to simplify as far as possible to make finding the second derivative easier.

thanks